Peran Bimbingan Dan Konseling Pribadi Sosial dalam mengatasi komunikasi lintas budaya siswa lama dan pendatang - Yusuf Hasan Baharudin (JCOSE Jurnal Bimbingan dan Konseling, 2022)
Every human being always communicates, because it becomes a very important part of life. Communication is used to deliver messages that come from the mind and heart will not be conveyed, but on the contrary with the existence of communication messages that are in the mind and heart can be conveyed, giving rise to the same meaning and goals that are well achieved. Likewise, the communication efforts of newcomer students to their new environment to be able to adapt. Likewise with the way of interaction or communication that occurs in old students and newcomers. Of course, it will be very different, apart from not being familiar with it, the environment and cultural habits are also different, especially with the pesantren atmosphere which is different from public schools. In this condition, it is important that individuals need to get personal social guidance and counseling assistance in helping the process of adaptation and interaction with their new environment. The purpose of this study was to determine the basic concepts of personal social guidance and counseling in helping immigrant students communicate and to find out the forms of communication difficulties for immigrant students. The contribution of this research is to contribute ideas about the importance of cross-cultural communication and the application of social guidance in assisting the communication patterns of newcomer students with their new environment and enriching the treasures of knowledge in the field of cross-cultural communication in both the educational and social spheres. In the preparation of this mini research, several research methods were used. So that in parsing and writing achieve the desired target. This mini research is a field research that seeks to find data directly in the field to be able to clearly identify what factors cause cross-cultural communication difficulties.